Intraarticular injection of autologous chondrogenic induced bone marrow stem cells promotes regenesis of traumatic osteoarthritis and promotes repair of meniscus injury in a sheep model - Alfaqeh, Hamoud Hussein Mohammed; Chua, Kienhui; MY , Norhamdan; HC, Chen; BS , Aminuddin; BHI , Ruszymah (2009)
Objective. The aim of this study was to determine if autologous bone marrow mesenchymal stem cells (AMSCs) cultured in chondrogenic medium containing growth factors could repair meniscus tissue and retard surgically induced osteoarthritis in the knee joint. Methods. Autologous Sheep bone marrow stem cells (AMSCs) were aspirated from sheep iliac crest and cultured in medium containing 5ng/ml TGFβ3 + 50ng/ml IGF-1 for 3 weeks. Six weeks after surgically induced osteoarthritis; a single dose of chondrogenic inducted AMSCs suspended in 5 ml Dulbecco’s Modified Eagle Medium (DMEM) at density of 10 million cells was injected intra-articularly into the osteoarthritic knee joint. After addition of another 6 weeks, the sheep were scarified and the femoral condyle and the proximal tibia were removed, fixed and photographed. The gross of the removed knee joint were graded by a blinded assessor based on ICRS grading system. Part of the tissue was imbedded in paraffin and sectioned into 5µm and stained with H&E and Safranin O. Result. The results indicated that surgically induced osteoarthritic knee joint treated with chondrogenic inducted AMSCs showed clear evidence of minimum articular cartilage destruction with meniscus repaired when compared with other control knee joints. Conclusion Our findings demonstrated that intra-articular injection of chondrogenic inducted AMSCs could stimulate regeneration of meniscal tissue and retards the progressive of osteoarthritis in sheep model.